INVESTIGASI EKSPERIMENTAL TERHADAP SIFAT MEKANIS CAMPURAN ASPAL MODIFIKASI POLIMER ETILEN-VINIL ASETAT DENGAN METODE CAMPURAN KERING - Daniel, Christian Gerald; Widjajakusuma, Jack; Widjaya, Valencio Stephen; Edricnes; Saputan, Clairine (Jurnal Jalan Jembatan, 2023)
This study aims to evaluate the impact of Ethylene-Vinyl Acetate (EVA) polymer modification in the dry mix method on the properties of asphalt components and asphalt-concrete mixtures. SEM and FTIR test images show the separation between polymer and bitumen. The VA fraction (carbonyl ring of bands 1600-2000 and 1080) affects the chemical composition of bitumen and produces properties that tend towards elasticity with little change in stiffness based on the DSR test. Air voids in the asphalt mixture were also reduced. Mixture stiffness, as seen from the modulus of elasticity and Marshall Quotient (MQ) values, increased by 20% and 50%, Marshall stability increased by 40%, tensile strength of mastic asphalt samples and asphalt concrete mixtures increased by up to 600% and 83.1% at low loading speeds, respectively. as well as 50% and 70% at high load speeds. This indicates that the mixed material is stiffer and stronger, especially on the mastic scale, where an asphalt mixture with an EVA content of 5% gives the best results. Fracture energy showed varying results, with the best value achieved at 5% EVA content for the asphalt mastic scale and 4% EVA for the asphalt concrete mix scale. A polymer content of 5% is recommended to produce a stiff, high-strength asphalt mixture. Key words: asphalt concrete, bitumen, dry mix method, ethylene-vinyl acetate, polymer-modified asphalt